Monitoring of a rehabilitated building in soft soil in Mexico and structural response to September 2017 earthquakes: Part 2: Numerical simulation. Issue 2 (December 2020) - Murià-Vila, David; Arnau Delgado, Oriol; Aguilar Silva, Guillermo G; Arias Lara, Damaris; Pérez-Liévana, Karen
This article deals with the proper numerical simulation of the response presented by an instrumented damaged-retrofitted building using a low computational cost linear-elastic model, using effective stiffness for its reinforced concrete structural members. The purpose is to identify the most appropriate criteria and considerations and to validate them against the actual behavior of the building registered during real earthquakes. Relevant structural aspects like concrete elastic modulus and soil–structure interaction effects are determined experimentally. Special attention is paid to select appropriate techniques to model the complex geometry of the North-South facades wall elements and their related coupling beams. Finally, time-history analyses of 20 March 2012 earthquake (service conditions demand) and 19 September 2017 earthquake (design conditions demand) are performed, both considering and ignoring the soil–structure interaction effects. Results point out that commonly adopted simplifications in numerical models of buildings must be correctly implemented to satisfactorily simulate their earthquake response.